Pembuatan Sistem Laporan Keuangan Sederhana Berbasis Microsoft Access untuk Usaha Mikro, Kecil, dan Menengah - Olivia Luthfia Nabila; Endang Asliana; Eksa Ridwansyah (Jurnal Ilmiah ESAI, 2022)
Micro, Small, and Medium Enterprises (UMKMs) are the largest business units in Indonesia. There are UMKMs that do not make transaction records and financial reports. This can be detrimental to business people because they do not know the details of transactions and developments in their own businesses and cannot take advantage of the usefulness of financial reports. This problem occurs because of the lack of ability to make financial reports and the absence of an effective, efficient, and affordable system. Technology is the right medium in dealing with these problems, therefore the author decided to create a simple financial reporting system based on Microsoft Access, called TEAMER. The analysis used in making TEAMER is quantitative analysis and Black Box Testing. The analysis shows that TEAMER has been running well according to the plans and orders entered. The author has succeeded in creating a system that can be used to enter business information, register accounts, and financial transactions, and can produce general journals, ledgers, and financial reports (cash flow, profit and loss, changes in capital and financial position).